'Not Just Another Anonymous Spot': Government Support for Memory Institutions in Prince Edward Island and Wales. (January 2016) - Lloyd, Simon
Abstract : In view of the important role that libraries, archives and museums – collectively referred to here as memory institutions – can play in regenerating communities that have faced economic and social difficulties, this essay examines government support for this sector in Prince Edward Island (PEI) through a comparative study with Wales. A historical sketch of the development of government administrative and planning capacity in this field in both Wales and PEI is offered, followed by a comparison of current funding commitments by each government. The study finds that relative funding levels are about the same in both jurisdictions, but that the Welsh government can offer an instructive example to the government of PEI through the former's commitment to planning for museums, archives and libraries, and for cultural and heritage activity as whole.